The Effect of Socialization through Video Education The Effect of Food Maturity Level on Food Nutritional Content - Wowon Maulana; Asep Bayu Dani Nandiyanto (Universitas Komputer Indonesia, 2022)
This education aims to invite the public to recognize food nutrition and its potential dangers if errors occur in food processing, namely a form of educational video-based learning media, for people who live in Cigugur Girang, Parongpong, Indonesia. The method used is by using educational video dissemination media to 10 adolescent adults in Cigugur Girang with an age range of 17-28 years. Respondents consisted of 4 women and 6 men. The research was conducted through three stages; (1) pre-test before providing education to respondents; (2) education through video media; (3) post-test after providing education to respondents. The results of this study indicate an increase in respondents' knowledge after the implementation of their actions. The results of the study are based on the N-Gain value which is known to be the average value (%). Based on the test value of T (-4.205) < T table (2.023) which means the value of the questionnaire increased not significantly. Based on the completion of this research, it is hoped that more people be able to find out by knowing the level of food maturity and nutritional content